Pengaruh Keberadaan Desa Wisata Tanon Kecamatan Getasan terhadap Ekonomi Masyarakat Lokal dan Guna Lahan - Puspita Ristiyana; Mohammad Muktiali (Jurusan Perencanaan Wilayah dan Kota, 2020)
Tanon Tourism Village is located in Dusun Tanon, Ngrawan Village, Getasan District, is one of the developing tourist villages in Semarang Regency. The Tanon Tourism Village was pioneered in 2009 and began to be formalized in 2012 as an embryo of a tourism village in Ngrawan Village. The development of the tourism village which has occurred for more than 10 years has influenced the physical and non-physical aspects of the village. The influence on physical aspects for example is the change in land, while the influence on non-physical aspects for example, on the economy of the community. So, this study aims to determine the effect of the presence of Tanon Tourism Village on the economy and land use. The method used is quantitative by using descriptive statistics and image analysis methods. Through the research results, it is known that its influence on the economic aspects is to encourage the desire to try, create employment opportunities, namely the creation of various jobs related to tourism village activities, as well as increasing the income earned every month. While the effect on land changes is a change in land use and land to meet the demand of accommodations and supporting facilities for tourism activities.